Development of Selective Inhibitors for Human Aldehyde Dehydrogenase 3A1 (ALDH3A1) for the Enhancement of Cyclophosphamide Cytotoxicity. Issue 5 (13th February 2014) - Parajuli, Bibek; Georgiadis, Taxiarchis M.; Fishel, Melissa L.; Hurley, Thomas D.
Abstract Aldehyde dehydrogenase 3A1 (ALDH3A1) plays an important role in many cellular oxidative processes, including cancer chemoresistance, by metabolizing activated forms of oxazaphosphorine drugs such as cyclophosphamide (CP) and its analogues, such as mafosfamide (MF), ifosfamide (IFM), and 4‐hydroperoxycyclophosphamide (4‐HPCP). Compounds that can selectively target ALDH3A1 could permit delineation of its roles in these processes and could restore chemosensitivity in cancer cells that express this isoenzyme. Here we report the detailed kinetic and structural characterization of an ALDH3A1‐selective inhibitor, CB29, previously identified in a high‐throughput screen. Kinetic and crystallographic studies demonstrate that CB29 binds within the aldehyde substrate‐binding site of ALDH3A1. Cellular proliferation of ALDH3A1‐expressing lung adenocarcinoma (A549) and glioblastoma (SF767) cell lines, as well as ALDH3A1 non‐expressing lung fibroblast (CCD‐13Lu) cells, is unaffected by treatment with CB29 and its analogues alone. However, sensitivity toward the anti‐proliferative effects of mafosfamide is enhanced by treatment with CB29 and its analogue in the tumor cells. In contrast, the sensitivity of CCD‐13Lu cells toward mafosfamide was unaffected by the addition of these same compounds. CB29 is chemically distinct from the previously reported small‐molecule inhibitors of ALDH isoenzymes and does not inhibit ALDH1A1, ALDH1A2, ALDH1A3, ALDH1B1, or ALDH2 isoenzymes at concentrations up to 250 μM. Thus, CB29 is a novel small molecule inhibitor of ALDH3A1, which might be useful as a chemical tool to delineate the role of ALDH3A1 in numerous metabolic pathways, including sensitizing ALDH3A1‐positive cancer cells to oxazaphosphorines.